Interaction between Constitutively Expressed Heat Shock Protein, Hsc 70, and Cysteine String Protein Is Important for Cortical Granule Exocytosis in Xenopus Oocytes() - Smith, Geoffrey B. (2005)
In many species, binding of sperm to the egg initiates cortical granule exocytosis, an event that contributes to a sustained block of polyspermy. Interestingly, cortical granule exocytosis can be elicited in immature Xenopus oocytes by the protein kinase C activator, phorbol-12-myristate-13-acetate. In this study, we investigated the role of cysteine string protein (csp) in phorbol-12-myristate-13-acetate-evoked cortical granule exocytosis. Prior work indicated that csp is associated with cortical granules of Xenopus oocytes. In oocytes exhibiting >20-fold overexpression of full-length Xenopus csp, cortical granule exocytosis was reduced by ~80%. However, csp overexpression did not affect constitutive exocytosis. Subcellular fractionation and confocal fluorescence microscopy revealed that little or none of the overexpressed csp was associated with cortical granules. This accumulation of csp at sites other than cortical granules suggested that mislocalized csp might sequester a protein that is important for regulated exocytosis. Because the NH(2)-terminal region of csp includes a J-domain, which interacts with constitutively expressed 70-kDa heat shock proteins (Hsc 70), we evaluated the effect of overexpressing the J-domain of csp. Although the native J-domain of csp inhibited cortical granule exocytosis, point mutations that interfere with J-domain binding to Hsc 70 eliminated this inhibition. These data indicate that csp interaction with Hsc 70 molecular chaperones is vital for regulated secretion in Xenopus oocytes.